Reengineering Java Game Variants into a Compositional Product Line: An empirical case study identifying activities and effort involved in a reengineering process - OSKAR, LIGNELL (My University, 2019)
Compositional Software Product Line Engineering is known to be tidious but powerful approach to migrate existing systems into SPL. This paper analyses the pros and cons of compositional SPLE strategies and also attempts to migrate five related Java games into an SPL while outlining the necessary activities to perform such migration. This paper also presents how to measure migration efforts of each activity. Lastly, the results of the migration process is compared to the result of another Master thesis that also conducts an SPL migration but using the annotative approach.
Keywords: Software Product Line; Reengineering; Migration